OPTIMALISASI EKSISTENSI BUDAYA LOKAL MELALUI PENDEKATAN ETHNOMATHEMATICS DALAM PEMBELAJARAN MATEMATIKA - Firdha Razak; Suradi Tahmir; Ahmad Thalib (STKIP Andi Matappa, 2024)
Learning mathematics that is relevant to local culture is an important factor in creating meaningful connections for students. Ethnomathematics, as an approach that integrates cultural values in mathematics learning, is the basis for efforts to increase students' understanding of mathematical concepts. In conducting literature analysis, the analytical descriptive method in the form of a review is used to review scientific sources about ethnomathematics and its application in mathematics education. These sources include journals, books and research articles. The review results show that the application of ethnomathematics allows students to relate mathematical concepts to their local cultural experiences. Cultural integration in mathematics learning also encourages students' interest in learning, increases motivation, and strengthens their sense of cultural identity. In conclusion, ethnomathematics is a tool for respecting and understanding cultural diversity, while enriching students' learning processes. The practical implications of this approach demonstrate the importance of considering cultural values in designing a more inclusive and diverse mathematics curriculum. Kata Kunci: Learning, Ethnomathematics, Local Culture